Sistema Doppler bidireccional para medición de flujo sanguíneo basado en una arquitectura abierta - García, F.; Moreno, E.; Solano, J.; Barragán, M.; Sotomayor, A.; Fuentes, M. (Revista Mexicana de Ingenieria Biomedica, 2003)
This paper describes the design of a continuous wave blood flow bidirectional Doppler system based on an open, high-resolution architecture that is portable and low-cost. The system incorporates the advantages of expensive systems with dedicated hardware. The system is composed of a flow detector probe, a signal conditioning stage, a direction detection module, a signal processing stage and a GUI. The direction detection of the signal is achieved using a fast digital Phasing Filter. The Doppler signal is processed by a Short-Time Fourier Transform-based algorithm. This is commonly used as a reference. Nevertheless, the system allows us to incorporate alternative high-resolution spectral estimation methods that might offer more precise information to the specialist